The Wall : The Real Costs of a Barrier between the United States and Mexico - Felbab-Brown, Vanda (Brookings essay (Brookings Institution), 2019)
In her Brookings Essay, The Wall, Brookings Senior Fellow Vanda Felbab-Brown explains the true costs of building a barrier along the U.S.-Mexico border, including (but not limited to) the estimated $12 to $21.6 billion price tag of construction. Felbab-Brown explains the importance of the United States' relationship with Mexico, on which the U.S. relies for cooperation on security, environmental, agricultural, water-sharing, trade, and drug smuggling issues. The author uses her extensive on-the-ground experience in Mexico to illustrate the environmental and community disruption that the construction of a wall would cause, while arguing that the barrier would do nothing to stop illicit flows into the United States. She recalls personal interviews she has had with people living in border areas, including a woman whose family relies on remittances from the U.S., a teenager trying to get out of a local gang, and others.